Współczesna wypowiedź dziennikarska w świetle zasady kooperacji - Kiklewicz, Aleksander (Stylistyka, 2020)
The author considers the use of H. P. Grice’s theory of cooperation to describe the verbal behavior in the public communication, particularly in journalism. First, the author argues that the public communication cannot be reduced either to cooperation or to rationally planned action. Second, the author describes not only the rhetorical implications, but also the interpersonal implications of lower and higher order (instrumental and global). In the separate sections, the author describes implementation of postulates of some categories: quality, quantity, relevance and manner in the contemporary journalistic texts.